2013
DOI: 10.1021/np4006579
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of the Heterobactin Siderophores from Rhodococcus erythropolis PR4 and Elucidation of Their Biosynthetic Machinery

Abstract: In this study, the isolation, the structural characterization, and the elucidation of the biosynthetic origin of heterobactins, catecholate-hydroxamate mixed-type siderophores from Rhodococcus erythropolis PR4, are reported. The structure elucidation of heterobactin A was accomplished via MS(n) analysis and NMR spectroscopy and revealed the noteworthy presence of a peptide bond between the guanidine group of an arginine residue and a 2,3-dihydroxybenzoate moiety. The two heterobactin S1 and S2 variants are der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 46 publications
(95 reference statements)
0
43
0
1
Order By: Relevance
“…The gene of a non-ribosomal peptide synthase was also induced by hydrocarbons. A recent study showed that this nonribosomal peptide synthase is responsible for the biosynthesis of heterobactins (Bosello et al 2013). Heterobactins are ironsiderophore molecules and their production has been reported in R. erythropolis and also in Nocardia tenerifensis (Carran et al 2001;Bergeron et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The gene of a non-ribosomal peptide synthase was also induced by hydrocarbons. A recent study showed that this nonribosomal peptide synthase is responsible for the biosynthesis of heterobactins (Bosello et al 2013). Heterobactins are ironsiderophore molecules and their production has been reported in R. erythropolis and also in Nocardia tenerifensis (Carran et al 2001;Bergeron et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There was also evidence that iron-binding siderophore systems derived from the colony microbiome were involved: a Firmicute acyl carrier protein putatively involved in siderophore production was enriched in puffs with particles ( Fig. 3F, p = 0.04), and a TonB dependent transporter (TBDT) for ferrienterochelin/colicins was identified only in puffs with particles 24 . This corroborates earlier evidence that though Trichodesmium does not produce its own siderophores, it acquires siderophore-bound iron produced via mutualistic interactions with epibionts, especially when provided with concentrated dust 8,25 .…”
Section: Resultsmentioning
confidence: 99%
“…Both of these ADAs, as well as one example of an MLP, are covalently fused to their A domains . In contrast, the vast majority of ADAs exist as independent proteins that are encoded by genes within their associated biosynthetic gene clusters or elsewhere in the genome . The frequency at which A domains require ADAs is now sufficient that their potential participation should be checked routinely.…”
Section: Methodsmentioning
confidence: 99%